Cookies Based on Sorghum Flour and Moringa Leaf Flour as a High Iron and Protein Source Supplementary Feeding (PMT) for Pregnant Women with Chronic Energy Deficiency (CED) and Anemia - Bahriyatul Ma'rifah; Arbian Revaldo Tauresta; Dewi Kusumawati (JURNAL RISET GIZI, 2026)
Background: Pregnant women with chronic energy deficiency (CED) have a 2.76-fold higher risk of developing anemia. Iron requirements can be met through supplementary feeding products formulated from iron-rich ingredients, such as sorghum flour and moringa leaf flour. Objective: To analyze the moisture content, ash content, macronutrient composition (protein, fat, and carbohydrates), micronutrient content (iron), and organoleptic properties of cookies formulated from sorghum flour and moringa leaf flour. Methods: This experimental study employed a Completely Randomized Design (CRD) with three formulations based on different ratios of sorghum flour to moringa leaf flour, i.e F1 (85 g : 15 g), F2 (80 g : 20 g), and F3 (75 g : 25 g). Data were analyzed using the Kruskal–Wallis test and One-Way ANOVA, followed by Duncan’s multiple range test. Results: The nutritional contents of F1–F3 were as follows: moisture 10.56–12.61%, ash 2.92–3.19%, protein 17.10–18.25%, fat 11.67–12.57%, carbohydrates 41.25–55.72%, and iron 10.49–13.29%. The best formulation, F3, had a brown color, moderately pleasant taste, less aromatic smell, non-crispy mouthfeel, and a fairly strong aftertaste. Each 60 g serving of F3 contained 242.56 kcal energy, 10.93 g protein, 7.24 g fat, 33.43 g carbohydrates, and 7.97 mg iron. Conclusion: F3 cookies met the standards for supplementary feeding products for pregnant women. However, their energy and fat contents were still below the recommended values and the Indonesian National Standard (SNI) for cookies. Each 60 g serving (4 pieces) contributed 10–15% of the Recommended Dietary Allowance (RDA) for pregnant women in the second trimester aged 19–29 years and could be classified as high in iron (39.09% NRV) and a source of protein (23.96% NRV).